Influence of Sucrose and Scoby Concentration on Physical Characteristics of Pineapple Skin Kombucha: Pengaruh Konsentrasi Sukrosa dan Scoby terhadap Karakteristik Fisik Kombucha Kulit Nanas - Rahmah Utami Budiandari; Andriani Eko Prihatiningrum; Rima Azara; Faiza Nur Aini (Universitas Muhammadiyah Sidoarjo, 2023)
This study investigates the impact of sucrose and Scoby concentration on the physical characteristics of kombucha made from pineapple skin juice. It was conducted using a randomized block design factorial with different sucrose and Scoby concentrations. The findings show that sucrose concentration significantly affected the total dissolved solids (TDS) of kombucha, while Scoby concentration had no significant effect. The highest TDS value was in the 5% sucrose concentration, and the lowest was in the 10% Scoby concentration. The study provides valuable insights for further research and applications in probiotic beverages and fermentation processes. Highlight: The study investigates the impact of sucrose and Scoby concentration on the physical properties of kombucha made from pineapple skin juice. Sucrose concentration significantly influences the total dissolved solids (TDS) of kombucha, while Scoby concentration shows no significant effect on TDS. The weight and thickness of the pellicle formed in kombucha are affected by both sucrose and Scoby concentrations, whereas the diameter remains unaffected. Keyword: Pineapple Skin, Kombucha, Sucrose Concentration, Scoby Concentration, Physical Characteristics.